Analysis of the population genetic structure of Rhynchophorus ferrugineus in Fujian, China, revealed by microsatellite loci and mitochondrial COI sequences. Issue 1 (14th February 2015) - Wang, Gui‐Hua; Zhang, Xiang; Hou, You‐Ming; Tang, Bao‐Zhen
Abstract The red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae: Rhynchophorinae), which is one of the most serious pests of palm plants, was first found in China in the city of Wenchang (Hainan Province) in the 1990s and has now expanded to South China, including Fujian Province. In this paper, we provide a genetic characterization and determine the genetic relationships among geographic populations of RPW in Fujian using microsatellite loci and cytochrome oxidase subunit Ι (COI) sequences. The results indicate a low‐level microsatellite diversity of RPW. Four genetic clusters of RPW were found in Fujian. No correlation was detected between the genetic and geographical distances in the microsatellite data. The mitochondrial COI sequence analyses revealed a high level of diversity in the Fujian populations. Eleven haplotypes were detected, and these included eight haplotypes that were different from those found earlier in Mediterranean, Middle East, Japanese, and other populations. Significant genetic variations were observed mainly within populations, both with microsatellites and with COI sequences. Low gene flow among the populations was observed. Our results indicate that the nuclear allelic diversity was low compared with the microsatellite results from populations in Wardan and Oman, but the mitochondrial diversity was not reduced to a similar extent. The low level of the genetic structure of RPW is related to the limited flight capacity of RPW and human‐aided dispersal rather than to the geographic distance.